Descriptive Analysis of Vo2max in Youth Soccer Athletes Using the Beep Test - Mariyal Qibtiyah; Andi Ummul Hairi; Irfan Yunus; Muhammad Naufal Ramadhansyah; Wirya Dipo Utama (CV Lentera Cendekia Indonesia, 2026)
Introduction: Aerobic endurance is a key determinant of performance in youth soccer, particularly during athlete selection and preparation for competition. Objective and practical fitness assessments are therefore required to identify athletes’ physiological readiness. This study aimed to describe the VO2Max profile of youth soccer athletes using the Multistage Fitness Test (MFT) or Beep Test. Methods: This quantitative descriptive study involved 65 male youth soccer athletes aged 15–17 years who participated in a regional selection program in Makassar, Indonesia, in September 2025. Aerobic endurance was measured using the Multistage Fitness Test. The validity of the MFT as a predictor of VO2Max has been widely reported in previous sports science studies. Data were analyzed descriptively using mean, median, standard deviation, minimum, maximum, and percentage distribution across fitness categories. Results: The descriptive statistical analysis showed that the athletes obtained a mean VO2Max score of 47.91 ± 4.89 ml/kg/min, with values ranging from 37.45 to 57.12 ml/kg/min. The highest predicted VO2Max value was 57.12 ml/kg/min, while the lowest was 37.45 ml/kg/min. Most athletes were classified in the “Good” category, indicating adequate aerobic readiness for youth-level competition. However, substantial variation was identified between athletes in the upper and lower performance groups, demonstrating unequal endurance capacity within the squad. Conclusion: The study confirms that the majority of athletes demonstrated adequate aerobic endurance, although several athletes remained below the expected competitive standard. The findings contribute practical baseline data for coaches in designing individualized endurance training programs, particularly High-Intensity Interval Training (HIIT), to reduce physical performance disparities within the team